Global atmospheric transport and source-receptor relationship for arsenic - Wai, Ka-ming; Wu, Shiliang; Li, Xueling; Jaffe, Daniel A.; Perry, Kevin D. (Environmental Science & Technology, 2016)
Arsenic and many of its compounds are toxic pollutants in the global environment. They can be transported long distances in the atmosphere before depositing to the surface, but the global source-receptor relationships between various regions have not yet been assessed. We develop the first global model for atmospheric arsenic to better understand and quantify its intercontinental transport. Our model reproduces the observed arsenic concentrations in surface air over various sites around the world. Arsenic emissions from Asia and South America are found to be the dominant sources for atmospheric arsenic in the Northern and Southern Hemispheres, respectively. Asian emissions are found to contribute 39% and 38% of the total arsenic deposition over the Arctic and Northern America, respectively. Another 14% of the arsenic deposition to the Arctic region is attributed to European emissions. Our results indicate that the reduction of anthropogenic arsenic emissions in Asia and South America can significantly reduce arsenic pollution not only locally but also globally.